Content validity and reliability of a food frequency questionnaire to measure eicosapentaenoic acid and docosahexaenoic acid intakes in young adults: a pilot study - Hanson, Jennifer Ann; Rosenkranz, Richard R.; Holcomb, Carol Ann; Haub, Mark D. (My University, 2012)
Background: The food environment is rapidly changing with regard to omega-3 fatty acids. Research is hindered by the lack of a tool specifically designed to measure intakes of long-chain omega-3 fatty acids in US populations. The purpose of this pilot study was to assess the content validity and reliability of a novel 14-item food frequency questionnaire (FFQ) designed to measure contemporary sources of eicosapentaenoic aid (EPA) and docosahexaenoic acid (DHA). Methods: During May of 2009, college students (n = 165) completed the FFQ and provided feedback. Forty-five completed the questionnaire a second time allowing for the evaluation of test-retest reliability. Results: None of the students reported consuming a food naturally rich in EPA and DHA that was not included in the FFQ. Overall instrument reliability (n = 54) was strong (ρ = 0.86, p < 0.001) and the reliability for each of the non-functional food items ranged from moderate to strong (ρ = 0.48 to 0.86, p < 0.001). Correlation coefficients for each of the functional food items were low and/or non-significant. Uncertainty regarding omega-3 functional foods was listed as a reason by eight of the twelve who felt one or more of the questions were difficult to answer. Conclusions: Overall instrument reliability was strong and content validity was good. Nonetheless, participant feedback, and the decreased test-retest coefficients for the omega-3 functional foods, suggests unfamiliarity may be problematic when measuring intakes from these food sources.
Keywords: Functional foods; n-3 fatty acids; Dietary assessment; Seafood; Eicosapentaenoic acid; Docosahexaenoic acid